Game‐theoretic beamforming techniques for multiuser multi‐cell networks under mixed quality of service constraints. Issue 5 (1st July 2017) - Basutli, Bokamoso; Lambotharan, Sangarapillai
Abstract : The authors propose a game‐theoretic approach for the downlink beamformer design for a multiuser multi‐cell wireless network under a mixed quality of services (QoS) criterion. The network has real time users (RTUs) that must attain a specific set of signal‐to‐interference‐plus‐noise ratios (SINRs), and non‐RTUs whose SINRs should be balanced and maximised. They propose a mixed QoS strategic non‐cooperative game wherein base stations determine their downlink beamformers in a fully distributed manner. In the case of infeasibility, they have proposed a fallback mechanism which converts the problem to a pure max–min optimisation. They further propose the mixed QoS bargain game to improve the Nash equilibrium operating point through Egalitarian and Kalai–Smorodinsky bargaining solutions. They have shown that the results of bargaining games are comparable to that of the optimal solutions.